6
Chat with our AI personalities
-3 + 9 +(-3) = -3 + 9 -3 = 3
All numbers are positive unless otherwise stated.
A positive number (+) sign is only shown if there is likely to be confusion.
A negative number (-) sign is invariably shown.
The addition of a negative number is equivalent to the subtraction of a positive number.
So +(-3) is equivalent to -(+3) which is written as - 3
10+11+9+3= 33
8/9 + 3/9 + 2/9 = 13/9 = 1 4/9
9+7+5+3+1 16+5+3+1 21+3+1 24+1 25
To work out the answer to 3 plus 3 x 3 - 3 plus 3, you add 3 and 3 together which is 9, multiply 9 by 3 which is 27, subtract 3 which is 24 and add 3 to get the answer which is 27.
It is: 9+(-3) = 6